Transformation of cultural landscape of Kyiv during the independence of Ukraine - A. H. Hladka (Ukrainian Cultural Studies, 2022)
The article is about a cultural analysis of Kyiv’s cultural landscape, which is made up of a complex of elements such as an architectural ensemble and public spaces, historical and cultural heritage objects, cultural and creative industries, media, along with external agents such as active consumers and contemplators. We observe the fundamental changes in Kyiv’s cultural landscape during the period of independence, as a result of modern changes in everyday culture. The article is based on multidisciplinary researches on the psychological space of Harry Trayandis, Sarah Dawkins, Sophia Nartova-Bochaver, visual anthropology of Benjamin Cope, Nerius Millerus, analysis of the transformation of leisure practices of Neil Brenchby-Barbury-Simbros and others. The scientific developments of Ernst Cassirer, Manuel Castells, Arnold Toynbee, and Tolcott Parsons are important core theories on which the methodology of work is built. The transformation in the overall cultural viewpoint may be seen in the development of urban cultural landscapes, as well as the increased emphasis on the production of cultural services. If the city used to be a "factory" for producing goods, it is now a market for services. Cities are becoming more and more places where cultural practices can be carried out. As a result, capital freely flows in the city, fueling the expansion of the cultural environment. Mapping residents’ daily cultural practices is evolving into a technique for mapping urban area and industries. Modern geographers like Neil Brenner, David Hervey, and others have recognized 1970s-era spatial alterations in Western cities. The city development, particularly its cultural environment, began with Ukraine’s independence in 1991. "Antropolis: wspóczesny Gdask w wymiarze symbolicznym" is a signifcant resource for us. It is a study of Gdansk’s urban anthropology from a German to a Polish city after the city’s architectural ensemble was demolished during WWII. The experience detailed in the essay is used to propose solutions for the rebuilding of Ukrainian cities. From 1991 to the present, a cultural investigation of the transformative processes of urban cultural landscapes and socio-culture phenomena in Kyiv and other Ukrainian cities has not been conducted. The cultural landscapes of Ukrainian cities are being transformed, and the cultural coordinates of local communities’ social engagement in the alteration of the cultural landscape of cities are being determined.